Use of Twitter among College Students for Academics: A Mixed-Methods Approach - Stefanie Amiruzzaman; Md Amiruzzaman (Social Sciences, 2022)
For almost a decade, Twitter use and its impact on students’ academic performance have been explored by many researchers. Despite growing scholarly interest, studies have been mostly quantitative in nature. The findings of previous studies are conflicting; thus, an in-depth study is needed to determine how and what impacts college students’ academic performance (i.e., GPA) when they spend time on Twitter. The purpose of this study was to understand the effects of Twitter use on college students’ academic performance. The present study shows that individual analysis techniques, such as quantitative or qualitative tools, are not enough to understand the underlying relationship. Therefore, a mixed-method approach (i.e., correlation and discourse analysis) was used to analyze the research data. Undergraduate students responded (N = 498) to a set of items along with some open-ended questions (n = 121). The results of this study indicate that how students use Twitter matters more than the amount of time they spend using it for their studies.